Relationship Between Hazrat Ali and Mawiyyah Ibn Abu Sufyan (Eurasian Journal of Humanities and Social Sciences, 2023)
This article talks about the relationship between Ali ibn Abu Talib and Muawiya ibn Abu Sufyan in the early days of the Arab caliphate, and tried to provide objective opinions and conclusions by focusing on the complex political situation between these two companions. This period is one of the most turbulent periods in the history of Islam. Some historians call it even the smallest civil war in the history of Islam. Actually, if we look at this period, we can see that there were some disagreements between Ali ibn Abu Talib and Muawiya I, and they found their solution over time.